Museums and Visitor Photography: Redefining the Visitor Experience - Stylianou-Lambert, Theopisti (My University, 2016)
Museums and Visitor Photography is based on new research and innovative practice in some of the world's leading museums. This handbook will help museum and gallery professionals to understand, connect with, and sympathetically manage visitors' participation - both in the museum and online. "A primer in using photography to document, experience, and share." Jeff Gates, Lead Producer, New Media Initiatives, Smithsonian American Art Museum. "A cornucopia of the latest research. This book will become a standard reference on the topic. A great volume."Ed Rodley, Associate Director of Integrated Media, Peabody Essex Museum. "Much-needed context to inform photography policies, practices, and programs... an essential resource." Dr. Randy C. Roberts, Deputy Director, Manetti Shrem Museum of Art, University of California, Davis. "Fresh perspectives for museum and photography studies." Dr. Annebella Pollen, Principal Lecturer, History of Art and Design, University of Brighton. "A fascinating in-depth look at visitor interaction and photography within the museum setting." Jeremy Sutton-Hibbert, Document Scotland.
Keywords: museums; visitor photography